Molluscum contagiosum in a girl with HIV infection. Case report and literature review. - Lomelí Valdez, R.; Olvera Suárez, A.; Gallegos Marin, J.A.; Del Vecchio, G.; Ordoñez Ortega, J.; Rodríguez Jurado, R.; Palacios López, C. (European Journal of Pediatric Dermatology, 2024)
Molluscum contagiosum (MC) is a common viral disease in the pediatric population characterized by smooth, shiny papules measuring a few millimeters. In immunosuppressed patients, these lesions can appear atypically, with multiple, extensive and verruciform appearance. We describe the case of a 7-year-old child diagnosed with human immunodeficiency virus (HIV) infection who, after stopping antiretroviral treatment, presented with multiple verruciform lesions on the scalp dating back a few months. Histological examination confirmed the diagnosis of MC. A topical treatment with 10% potassium hydroxide reduced the lesions which were then removed with curettage. A literature review is also performed including pathogenesis, clinical manifestations and treatment options in children with HIV infection.